Non-linear effects of oil shocks on stock prices - Haroon Mumtaz; Ahmed Pirzada; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2018)
This paper uses a panel Threshold VAR model to estimate the regime-dependent impact of oil shocks on stock prices. We find that an adverse oil supply shock has a negative effect on stock prices when oil inflation is low. In contrast, this impact is negligible in the regime characterised by higher oil price inflation. Using a simple DSGE model, we suggest that the explanation for this result may be tied to the behaviour of credit spreads. When oil inflation is low, lower policy rates encourage firms to get highly leveraged. A negative oil shock in this scenario leads to a substantial increase in spreads, reducing profits and equity prices. In contrast, at higher rates of inflation, spreads are less affected by the oil shock, ameliorating the impact on the stock market.
Keywords: 330; Threshold VAR; Hierarchical Prior; DSGE model; Oil shocks